Leiomyoma - Abduljabbar, Hassan (IntechOpen, 2020)
Leiomyoma of the uterus is a benign tumor of the smooth muscle. It is the most common pathologic abnormality of the female genital tract. It is found in 20 - 50% of women older than 30 years but is rare in children and post-menopausal women. It can present as an asymptomatic pelvic mass or as abnormal vaginal bleeding, or it may be associated with painful urinary symptoms, sexual dysfunction and dyspareunia, infertility, and recurrent pregnancy loss. The etiology of uterine fibroids is unclear. Diagnosis by clinical history and physical examination, pelvic examination, ultrasound pelvis and CT scan, and MRI are helpful. Management can be medical hormonal or non-hormonal, open surgical, endoscopic, or uterine artery embolization.